THE SYNERGY OF INDONESIA’S MARITIME POWER INSTRUMENT TO FACE CHINA’S CLAIM OVER SOUTH CHINA SEA - Sidjabat, Christine Anggi; Octavian, Amarulla; Said, Budiman Djoko (Indonesia Defense University, 2018)
Despite the fact that Indonesia is not one of the claimant states, China’s provocation through its fishing boats escorted by Chinese Coast Guard has been violating Indonesia Exclusive Economic Zone on South China Sea (SCS) which intersects with Nine Dashed Line (NDL). Up to this day, the synergy among Indonesian maritime power instruments to defend Indonesia’s sovereign rights is still weak, thus the problem identified in this research is how the instrument of power authorized in Indonesia’s maritime domain synergizes to face China’s claim over SCS. Synergy analysis is seen from three aspects: perspective, policy, and Rules Of Engangement (ROE) applied to operational. This research uses qualitative method to further explore the research question, with Soft System Methodology technique to approach the problems through comparison between system of thought and real world in a structured manner, as well as supported by NVivo to execute the process of data triangulation. Research results show that Indonesia’s maritime power instrument have not a harmonious perspective on NDL yet. This study also shows that policy created by policy makers and strategic derivatives created by strategy makers of the Government of the Republic of Indonesia have not been in harmony, thus appropriate ROE at operational level to face China's provocation on the SCS has not been formulated by adjusting authority with instrument capability. Overall, the study found that the synergy of Indonesia’s maritime power instruments is not yet reliable to deal with China’s Claims over the territory of Indonesia in the SCS.Keywords: Synergy, Maritime Power Instruments, Nine Dashed Line, South China Sea, Sovereign Rights